SIFIDE II: How effective is it at promoting innovation? - Miguel Eduardo Milagre de Almeida Santos (2021)
Portugal, like other EU countries, announces and promotes several public policies to foster innovation in a business context (Guedes de Oliveira, et al., 2019). One such policy consubstantiates in a fiscal incentive to the values invested by companies, currently known as SIFIDE II. This piece of work was born out of the curiosity to better understand the practical translation this measure, dating back from 1997, has in the Portuguese companies. Through a literature review, questionnaires to companies and the conduction of a focus group, we sought to understand the conformity between the intentions of the lawmaker and the practices and perceptions of companies, duly contextualized. Our findings suggest SIFIDE II suffers from being poorly adopted and that its promotion policy is at least debatable. Finally, we conclude that SIFIDE II has the potential for improvement.